2003
DOI: 10.1073/pnas.0337331100
|View full text |Cite
|
Sign up to set email alerts
|

PPARδ is a very low-density lipoprotein sensor in macrophages

Abstract: Although triglyceride-rich particles, such as very low-density lipoprotein (VLDL), contribute significantly to human atherogenesis, the molecular basis for lipoprotein-driven pathogenicity is poorly understood. We demonstrate that in macrophages, VLDL functions as a transcriptional regulator via the activation of the nuclear receptor peroxisome proliferator-activated receptor ␦. The signaling components of native VLDL are its triglycerides, whose activity is enhanced by lipoprotein lipase. Generation of peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
209
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(221 citation statements)
references
References 46 publications
11
209
1
Order By: Relevance
“…Similar compensatory changes in the expression of genes that increase hepatic cholesterol have been observed in mice overproducing liver derived HDL (54). Recently, it was reported that VLDL-TG hydrolyzed by LPL strongly activates the expression of a series of "lipid storage" genes in macrophages via PPAR␤, indicating that PPAR␤ is a VLDL sensor in these cells (55). It is conceivable that, in the absence of PPAR␤, extrahepatic cells such as macrophages, are unable to properly detect or uptake lipids found in VLDL and the increased hepatic production of VLDL represents a compensatory response.…”
Section: Ppar␤-null Mice On An Hf Diet Exhibit Lowered Body Weight Anmentioning
confidence: 60%
“…Similar compensatory changes in the expression of genes that increase hepatic cholesterol have been observed in mice overproducing liver derived HDL (54). Recently, it was reported that VLDL-TG hydrolyzed by LPL strongly activates the expression of a series of "lipid storage" genes in macrophages via PPAR␤, indicating that PPAR␤ is a VLDL sensor in these cells (55). It is conceivable that, in the absence of PPAR␤, extrahepatic cells such as macrophages, are unable to properly detect or uptake lipids found in VLDL and the increased hepatic production of VLDL represents a compensatory response.…”
Section: Ppar␤-null Mice On An Hf Diet Exhibit Lowered Body Weight Anmentioning
confidence: 60%
“…Prostaglandin A1 (PGA1), PGD2 and PGD1 can activate PPARβ/δ in reporter assays [27]. Similar to PPARα and γ, incubation of triglyceride rich lipoproteins with LPL results in the production of PPARβ ligands [28,29]. We have shown here that several molecules present in oxVLDL including 15-HETE, 13(S)-HODE and 4-HNE are agonists of PPARβ/δ ( Fig.…”
Section: Discussionmentioning
confidence: 78%
“…27) VLDL, which is also a triglyceride-rich lipoprotein particle, functions as a transcriptional regulator via activation of the PPARδ in macrophages. 28) PPARδ is also one of the target genes of Wnt signaling, which is relevant to carcinogenesis. 29) Therefore, high levels of serum triglyceride and VLDL may enhance the growth of intestinal polyps in Apc-deficient mice through activation of PPARδ in their intestines.…”
Section: Discussionmentioning
confidence: 99%